Pulling Apart the Apparatus - Straw, Will (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2011)
This article responds to a series of questions posed by Francesco Casetti to “Impact” conference panelists dealing with the fate of apparatus theory in film studies. I argue that the unravelling of apparatus theory has been a long, complex process, unfolding over four decades. A well-known feature of this unravelling within English-language film studies has been the assertion that spectators/subjects are not formal products of the functioning of an apparatus, but rather embodied individuals characterized by multiple forms of identity. This assertion has helped to detach the study of film spectatorship from theories of the apparatus, rendering the former more empirical and sociological. At the same time, difficulties in translation have resulted in a confusion, in English-language film scholarship, between the French terms appareil and dispositif, both of which have found themselves translated as “apparatus”. Drawing on the writings of Agamben and Vouilloux, I show how a key problem in apparatus theory is the extent to which the forces shaping spectator identity are themselves part of an apparatus or might be seen as external to the latter and as historical variables with which an apparatus interacts.